2016
DOI: 10.1016/j.jval.2016.09.1488
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Potential Risk Factors, Sequelae of Diastasis Recti Abdominis and The Treatment

Abstract: A605of treatment, where the training of the transverse abdominis muscle was stressed. Pearson product moment correlations, ANOVAs and paired sample t-tests were used to examine relationship. P < 0.05 was considered statistically significant. Results: The prevalence of DRA in our population was 46.5%. There was a measurable difference between the DRA and age (p= 0.099), BMI (p= 0.129), number of pregnancies (p= 0.126), and type of delivery (p= 0.058). The results between the number of deliveries and the IRD wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
1
19
0
2
Order By: Relevance
“…At present, there are few studies using CT to judge the occurrence of DRA. Previous study showed that the incidence of DRA in women was as high as 46.5% to 100% in the third trimester and 30% to 70% postpartum (Fernandes da Mota et al, 2015; Gitta et al, 2017); Kimmich et al, 2015). Other studies have shown that vaginal births have a lower risk of postpartum DRA than caesarean deliveries (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…At present, there are few studies using CT to judge the occurrence of DRA. Previous study showed that the incidence of DRA in women was as high as 46.5% to 100% in the third trimester and 30% to 70% postpartum (Fernandes da Mota et al, 2015; Gitta et al, 2017); Kimmich et al, 2015). Other studies have shown that vaginal births have a lower risk of postpartum DRA than caesarean deliveries (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…The rectus abdominis plays an important role in posture, trunk and pelvis stability, respiration, trunk movement and abdominal organ support (Benjamin et al, 2014). For these reasons, DRA may contribute to chronic low back pain (Doubkova et al, 2018), have an impact on life (Gitta et al, 2017) and require surgery (Cheesborough, & Dumanian, 2015). There is an intervention research showing that postpartum back pain will be alleviated, muscle elasticity will be increased, and maternal body will recover as soon as possible when DRA condition improves (Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRA usually regresses to its prepregnancy width, but the condition persists in 32–46 per cent of postpartum women. Reported risk factors for persistent DRA include maternal age, multiparity, caesarean section, macrosomia and multiple gestations.…”
Section: Introductionmentioning
confidence: 99%
“…Such skin redundancy and fascial laxity in the abdominal area has been shown to cause back strain and pain [14]. According to Gitta et al [15] not just low back pain but also decreased quality of life may occur in patients with DRA.…”
Section: Introductionmentioning
confidence: 99%